Level of Understanding Among Parents and Teacher for The National Preschool Standard Curriculum (KSPK) - Muhammad Nazri Bin Abdul Rahman; Nurul Hidayah Binti Norhamidi (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study is aimed to know the perception of teachers towards the level of understanding of The National Preschool Standard Curriculum (KSPK) among teachers and parents. The data was collected through in-depth interviews by two preschool teachers from a private and government preschool. The interviews were documented through email that covers the level of teachers understanding, teaching practice and the perception of teachers on parents understanding. Then, the data were analyzed using thematic analysis by manually organizing and analyzing data for accurate monitoring. Studies show that both preschool teachers understand the KSPK 2017 but for parents, there are only a few parents who understand the KSPK and still prioritizing on academic matters only.